Comparative analysis of reconciliation procedures in Syariah and Civil courts - Mohd Nor, Aishah; Muhammad Hashim, Nurhidayah; Rahmat, Nur Ezan; Md Hashim, Noraini; Kusrin, Zuliza; Abdul Majid, Latifah; Bahari, Norai'nan (Secholian Publication PLT, 2022)
Reconciliation in divorce proceedings has been introduced in family courts in dealing with application for divorce. This study focuses on the functions, the appointment of committees, and the procedures of reconciliation in Shariah courts and Civil courts to compare the practice of laws between Section 47(5) to (17) of the Islamic Family Law (State of Selangor) Enactment 2003 (IFLSE 2003) and Section 106 of the Law Reform (Marriage and Divorce) Act 1976 (LRA 1976). This study was conducted through doctrinal and comparative legal research of the existing literature, including academic articles, statutes, and case laws relating to reconciliation. The findings establish the similarities and differences of both statutes. This study suggests that a reconciliation before a legal proceeding may employ a subtler approach for out-of-court negotiation leading to potentially better results